Pengaruh Pengungkapan Environmental, Social, dan Governance (ESG) Terhadap Kinerja Perusahaan Energi dan Pertambangan - Annisa Nur Fitria; Mariana Mariana (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The rising levels of greenhouse gas emissions, environmental crises, and social conflicts in the energy and mining sectors underscore the urgency of adopting sustainability principles through environmental, social, and governance (ESG) disclosures. This study aims to examine the relationship between the intensity of ESG disclosure and corporate performance, as measured by the Return On Assets (ROA). A quantitative approach was employed using secondary data obtained from annual and sustainability reports of 37 energy and mining companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The sample was selected through purposive sampling based on the completeness of ESG reporting in accordance with GRI standards. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The findings reveal that environmental and social disclosures are associated with corporate performance, while governance disclosure does not show a significant relationship. These results highlight the need to strengthen the substance and implementation of sustainability-oriented governance practices. This study recommends ongoing evaluation of ESG reporting practices and the adoption of more comprehensive measurement indicators to enhance overall corporate performance.